1983
DOI: 10.1139/f83-091
|View full text |Cite
|
Sign up to set email alerts
|

An Energetics Model for Lake Trout, Salvelinus namaycush: Application to the Lake Michigan Population

Abstract: An energetics model is implemented for lake trout, Salvelinus rzarnaycush, and applied to the Lake Michigan population. It includes an egestion function allowing any proportional mix of fish and invertebrates in the diet, a growth model accounting for both ontogenetis and seasonal changes in energy-density of predator and prey, a model for typical in situ swimming speed, and reproductive energy losses due to gametes shed. Gross conversion efficiency of energy by lake trout over their life (21 .$%) is about twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
347
2
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(377 citation statements)
references
References 11 publications
12
347
2
6
Order By: Relevance
“…The observed FBW in TC max and TC was significant lower than the predicted FBW. The over-estimation in the feeding chart by the bioenergetics modeling in present study could be due to the following errors and needed to be improved in the extended studies: 1) Errors are from the function of energy content and body weight (Kitchell et al, 1977;Stewart et al, 1983;Cui and Wootton, 1989). 2)Errors are from the prediction of growth by specific growth rate in energy.…”
Section: Discussionmentioning
confidence: 89%
“…The observed FBW in TC max and TC was significant lower than the predicted FBW. The over-estimation in the feeding chart by the bioenergetics modeling in present study could be due to the following errors and needed to be improved in the extended studies: 1) Errors are from the function of energy content and body weight (Kitchell et al, 1977;Stewart et al, 1983;Cui and Wootton, 1989). 2)Errors are from the prediction of growth by specific growth rate in energy.…”
Section: Discussionmentioning
confidence: 89%
“…Ils s'avèrent des outils de gestion intéressants pour décrire, quantifier et éventuellement prédire les variations énergétiques à l'intérieur des stocks de poissons. Ils servent entre autre à évaluer l'impact des prédateurs sur les proies (Stewart et al 1983;Hartman et Margraf 1992). Ils sont également utilisés pour répondre à d'autres questions sur des sujets tels que la relation entre la quantité de nourriture ingérée et la croissance (Kitchell et al 1977), les effets des changements climatiques sur les poissons (Hill et Magnuson 1990), le cycle des nutriments dans les lacs (Schindler et al 1993;Kraft 1993) ou la bioaccumulation de polluants dans les poissons (Mather et Johansen 1985).…”
Section: Mise En Garde/adviceunclassified
“…Ils sont également utilisés pour répondre à d'autres questions sur des sujets tels que la relation entre la quantité de nourriture ingérée et la croissance (Kitchell et al 1977), les effets des changements climatiques sur les poissons (Hill et Magnuson 1990), le cycle des nutriments dans les lacs (Schindler et al 1993;Kraft 1993) ou la bioaccumulation de polluants dans les poissons (Mather et Johansen 1985). L'élaboration des modèles bioénergétiques repose essentiellement sur une équation balancée où l'énergie acquise lors de l'alimentation (consommation) est égale à la sommation de l'énergie allouée pour les différentes activités physiologiques telles que le métabolisme standard, la digestion, la croissance, l'activité, l'excrétion urinaire et les pertes fécales (Bagenal 1978;Kitchell et al 1977;Stewart et al 1983;Beauchamp et al 1989;Hewett et Johnson 1992 (Scott et Crossman 1974;Bernatchez et Giroux 2000). Il a été démontré qu'au réservoir Horsetooth, au Colorado, l'éperlan arc-en-ciel peut représenter une proportion importante de la diète de ce prédateur et pourrait affecter sa croissance (Jones et al 1994 (Jones et al 1979).…”
Section: Mise En Garde/adviceunclassified
See 1 more Smart Citation
“…Pacific lamprey is extraordinarily rich in fats, much richer than salmon. Caloric values for lamprey range from 5.92 to 6.34 kcal/g wet weight (Whyte et al 1993), whereas salmon average 1.26 to 2.87 kcal/g wet weight (Stewart et al 1983). In fact, the work of Roffe and Mate (1984) revealed that the most abundant dietary item in seals and sea lions was Pacific lamprey.…”
Section: Ocean Lifementioning
confidence: 99%